Transformasi Digital terhadap Sumber Daya Manusia sebagai Upaya Meningkatkan Kapabilitas Perusahaan - Angelika Yanuar Kirana; Mohamad Saifudin; Muhammad Miftachul Mukhlisin; Nina Fatmawati; Mochammad Isa Ansori (Universitas 45 Surabaya, 2023)
Technological and industrial developments require qualified human resources in every company, strong companies are able to survive all forms of change and challenges of the times. Currently, companies must be able to anticipate and adapt to technological developments and one of the most important assets of a company is its human resources because this affects the survival of the company. The results of the literature review show that human resources have a significant influence on digital transformation, especially through increasing company capabilities. By using an HR quality assessment based on knowledge, skills, expertise and behavior, organizations can accurately determine how to improve the capabilities of each employee. To support objective performance assessment, a balance of qualified human resources is needed, and resource support will facilitate objective performance assessment. In the digital human resource transformation process, the optimization of a company's human resource capacity is measured through the knowledge, skills, expertise and behavior of the company's employees. By paying attention to the impact of performance, businesses can design strategies to achieve goals supported by digital transformation. This research presents an objective view of how to improve a company's human resource capabilities through digital transformation. Focusing on the digital era, this article provides knowledge about the importance of more accurate and effective decision making in human resource management. The aim of this article is to provide an effective combination to improve a company's HR capabilities during this complex digital transformation.